Cloning, purification and biochemical characterization of two β-N-acetylhexosaminidases from the mucin-degrading gut bacterium Akkermansia muciniphila. (2nd March 2018) - Wang, Meng; Zhang, Xiao-Yang; Guo, Rui-Rui; Cai, Zhi-Peng; Hu, Xiao-Chun; Chen, Huan; Wei, Shuang; Voglmeir, Josef; Liu, Li
Abstract: Two genes encoding the β- N -acetylhexosaminidases Am2301 and Am2446 were cloned successfully from the mucin-degrading bacterium Akkermansia muciniphila. The recombinant enzymes with molecular masses of 61 kDa and 78 kDa were isolated and biochemically characterised. The optimum temperature of both enzymes was 37 °C, and the optimum pH was determined to be pH 5.0 for Am2301 and pH 6.5 for Am2446. The addition of sodium dodecyl sulphate (SDS) reduced the enzymes' activity significantly. Cu 2+ -ions decreased the activity of Am2301 by 70%, while the activity of Am2446 was significantly reduced by Fe 3+ -ions. PugNAc strongly inhibited both enzymes already in the sub-micromolar concentration range. The enzymes catalysed the hydrolysis of β1, 4-linked N -acetylgalactosamine and β1, 6-linked N -acetylglucosamine from glycan standards, as well as β1, 2-linked N-acetylglucosamine units from the non-reducing end of N -glycans. The present study describes the first functional characterisation of β- N -acetylhexosaminidases from this human gut symbiont. Graphical abstract: Highlights: Two putative β-N-Acetylhexosaminidases from a human gut bacterium were cloned and recombinantly expressed in active form. Functional characterisation revealed that the enzymes had similar temperature optima, metal requirements and pH optima. The enzymes showed similar substrate specificities towards various glycan substrates. Simple expression and purification procedures make these enzymes valuable for bioanalytical applications.